Kondisi Depresi, Stres dan Cemas Pasien Gagal Ginjal yang sedang Menjalani Hemodialisis - Juandri Seprianto Tusi; Ni Made Merlin; Antonius Rino Vanchapo (Faletehan Health Journal, 2023)
The number of patients with kidney failure is increasing every year. Nowadays, kidney failure was not only caused by several chronic diseases but also lifestyle and a history of urinary tract infections. The purpose of this study was to examine the condition of depression, stress and anxiety of patients with kidney failure undergoing hemodialysis in hospital. This research was descriptive with survey research design. The sampling technique used a non-probability sampling, namely purposive sampling. The respondents were 40 patients with kidney failure undergoing hemodialysis. The research variables were depression, stress and anxiety. The instrument used in this study was the questionnaire of Depression, Anxiety, and Stress Scales 42 items (DASS-42). The data were analyzed by Statistical Packages for the Social Sciences (SPSS) application and presented by using central tendency. This study also paid attention on some research ethics, namely anonymity, justice, and non-maleficence. The results showed that most respondents experienced a moderate depression, a severe stress, and a severe anxiety. In addition, recently the incidence of chronic kidney failure is possibly experienced by young adults and early twenty years patients.